CISSP exam guide - Harris, Shon; Maymí, Fernando (New York : McGraw-Hill Education, 2019)
"Thoroughly updated for the latest release of the Certified Information Systems Security Professional exam, this comprehensive resource covers all exam domains, as well as the new 2018 CISSP Common Body of Knowledge developed by the International Information Systems Security Certification Consortium (ISC)2. CISSP All-in-One Exam Guide, Eighth Edition features learning objectives at the beginning of each chapter, exam tips, practice questions, and in-depth explanations. Written by leading experts in information security certification and training, this completely up-to-date self-study system helps you pass the exam with ease and also serves as an essential on-the-job reference"--
Includes bibliographical references and index.
oif 16/12/2019
Loans
Keywords: Computer networks; Telecommunications engineers